2006
DOI: 10.2486/indhealth.44.531
|View full text |Cite
|
Sign up to set email alerts
|

Possible Broad Impacts of Long Work Hours

Abstract: The paper summarizes research linking long work hours to a wide range of risks to workers, families, employers, and the community. The risks are theorized to stem from less time to recover from work, longer exposure to workplace hazards, and less time to attend to non-work responsibilities. Risks to workers include sleep deprivation, poor recovery from work, decrements in neuro-cognitive and physiological functioning, illnesses, adverse reproductive outcomes, and injuries. Risks to families include delayed mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
131
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(147 citation statements)
references
References 73 publications
9
131
0
7
Order By: Relevance
“…The mechanisms by which long working hours increase the risk of CVD have been explained previously in detail. One possible explanation is that the risk of CVD increases when working long hours because sleep duration decreases, and therefore time for recovery also decreases, creating poor lifestyle habits 19) . Another possible mechanism is that long working hours increase job-related stress 20) .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which long working hours increase the risk of CVD have been explained previously in detail. One possible explanation is that the risk of CVD increases when working long hours because sleep duration decreases, and therefore time for recovery also decreases, creating poor lifestyle habits 19) . Another possible mechanism is that long working hours increase job-related stress 20) .…”
Section: Discussionmentioning
confidence: 99%
“…However, although several reviews of this field exist (5,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), the few systematic quantifications of the evidence have been based on published cross-sectional (18,19,25) or published longitudinal studies (26). Given the potential publication bias in studies based on published data (27), an individual-participant metaanalysis of unpublished data would provide important complementary evidence to evaluate the effect of long working hours on mental health.…”
mentioning
confidence: 99%
“…First, with respect to working structures, sleep disturbances may be associated with or mediated by irregular working schedules. In the United States it is estimated that about one fifth of employees are shift workers 6,7) and lifestyle changes have increased the demand for a 24/7 service, particularly within the service industry 8) . Second, with respect to psychological factors, results from an investigation of 8,700 Japanese local government and transit company employees showed that occupational stress was a possible risk factor for insomnia 9) .…”
Section: Introductionmentioning
confidence: 99%